PENGARUH VARIASI JARAK DETEKTOR, LUAS LAPANGAN RADIASI DAN POSISI DETEKTOR DARI PUSAT BERKAS RADIASI MENGGUNAKAN MULTI PURPOSE DETECTOR (MPD) PADA PENGUKURAN TEGANGAN SINAR-X - Evi Handriani Bertua Simamora; Choirul Anam; Evi Setiawati (Youngster Physics Journal, 2013)
An evaluation of the distance effect of Multi-Purpose Detector (MPD)-X ray source, variations of field size of radiation and position of the MPD on the X-ray voltage measured, have been done. There are necessary because they have not been recommended from the MPD procedure manual yet. The detector operated at voltage of 70 kV and current-time of 12.5 mAs. The measurement of voltage using MPD from RTI Electronics product. It is multifunction detector that can measure dose and voltage invasively. The previous step is measurement of dose for ensure correct equipment setting. These measurements is done for several variations such as MPD-X ray distance of  60 - 160 cm, field sizes 0f 4x4 cm - 40x40 cm2, detector's position of 0 (at center of beam) and 1-11 cm from centre of beam.   The results are obtained that the voltage that measured is not affected by all of variation values such as distance difference of MPD-X ray source,  field sizes and detector's position. Furthermore, for measurement of outside of radiation beam, MPD   can still measur voltage with good validation. Therefore, the measurement of voltage using MPD has high flexibility because it is not influenced by set up measurement.Keywords: The X ray voltage measurement, Multi-Purpose Detector (MPD), Barracuda.